Precalculus (10th Edition)

Published by Pearson
ISBN 10: 0-32197-907-9
ISBN 13: 978-0-32197-907-0

Chapter 6 - Trigonometric Functions - Chapter Review - Cumulative Review - Page 437: 8



Work Step by Step

To find the inverse: rewrite $f(x)$ as $y$, then exchange $x$ and $y$, and finally solve the equation for $y$. Hence here: $y=3x-2\\x=3y-2\\x+2=3y\\y=\frac{x+2}{3}=f^{-1}(x)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.